Microsoft Excel VBA and macros : (Office 2021 and Microsoft 365) - Jelen, Bill; Syrstad, Tracy (Pearson Education, Inc., 2022)
Renowned Excel experts Bill Jelen (MrExcel) and Tracy Syrstad help you automate Excel tasks to get more done, faster than ever. Use this guide to automate virtually any routine Excel task: save yourself hours, days, maybe even weeks. Make Excel do things you thought were impossible, discover macro techniques you wont find anywhere else, and create automated reports that are amazingly powerful. Bill Jelen and Tracy Syrstad help you instantly visualize information to make it actionable; capture data from anywhere, and use it anywhere; and automate the best new features in Microsoft Excel. Youll find simple, step-by-step instructions, real-world case studies, and 50 workbooks packed with examples and complete, easy-to-adapt solutions.